Case Report: A case of first-line treatment for rare ROS1 fusion mutation lung adenocarcinoma with entrectinib - Yang, Yifan; Yi, Qing; Yang, Wei; Luo, Yongzhong; Zhang, Lemeng (Frontiers in Oncology, 2025)
The incidence of the ROS1 fusion mutation (ROS proto-oncogene 1) in non-small cell lung cancer (NSCLC) is approximately 1-2%. At least 55 partner genes have been identified that can fuse with ROS1.Herein, we report a case of a lung adenocarcinoma patient harboring a rare ROS1 fusion mutation with brain metastasis, who achieved good control of both lung and intracranial lesions after treatment with Entrectinib. A 68-year-old female patient with no smoking history presented with a cough and headache. She was diagnosed with advanced lung adenocarcinoma, stage T1cN3M1c IVb, which included multiple brain metastases. An IGR (downstream MAN1A1) ROS1:exon34 fusion was detected at a mutant allele frequency (MAF) of 12.73%, accompanied by two TP53 mutations c.1024C>T (p.R342*) and c.686_687del (p.C229Yfs*10). The resultant fusion protein preserves the whole TRKA kinase domain of ROS1, and therefore may constitutively activate ROS1.Therefore, RNA-seq was conducted to further confirm the expression of IGR-ROS1 fusion at mRNA level. A CD74:exon6 ~ ROS1: exon 35 fusion was identified, which could mediate the full kinase function. A biopsy of the right supraclavicular lymph node confirmed the diagnosis of lung adenocarcinoma. She was diagnosed with advanced lung adenocarcinoma, stage T1cN3M1c IVb, which included multiple brain metastases. The patient began treatment with entrectinib (600 mg, once daily) as a first-line therapy. At the time of diagnosis, the patient reported headaches and experienced sleep disturbances. Subsequently, the patient underwent whole-brain radiotherapy. Significant improvements were noted in her headache and insomnia symptoms. After one month, the longest diameter of the left upper lung nodule decreased from 19 mm to 12 mm, and there was a notable reduction in the right hilar and mediastinal lymph nodes. Additionally, the patient’s intracranial metastatic lesion reduced in size from 19 mm to 8 mm, leading to an improvement in her headache symptoms. It is worth further exploring whether patients carrying IGR fusions can receive targeted therapy.